Homologous and Heterologous Boosting of the Chadox1-S1-S COVID-19 Vaccine With the SCB-2019 Vaccine Candidate: A Randomized, Controlled, Phase 2 Study. (16th August 2022) - Costa Clemens, Sue Ann; Milan, Eveline Pipolo; Sprinz, Eduardo; Neto, José Cerbino; Pacciarini, Filippo; Li, Ping; Chen, Hui Ling; Smolenov, Igor; Pollard, Andrew; Clemens, Ralf
Abstract: Background: Ongoing outbreaks of coronavirus disease 2019 (COVID-19) are driven by waning immunity following primary immunizations and emergence of new severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants that escape vaccine-induced neutralizing antibodies. It has been suggested that heterologous boosters could enhance and potentially maintain population immunity. Methods: We assessed the immunogenicity and reactogenicity of booster doses of different formulations of aluminium hydroxide–adjuvanted SCB-2019 vaccine (9 μg of SCB-2019, with or without CpG-1018 adjuvant, or 30 μg of SCB-2019 with CpG-1018) in Brazilian adults primed with ChAdOx1-S vector vaccine. S-protein antibodies and ACE2-binding inhibition were measured by enzyme-linked immunosorbent assay (ELISA) on days 1, 15, and 29. Participants self-reported solicited adverse events and reactions. Results: All SCB-2019 formulations increased S-protein ELISA antibodies and ACE2 binding inhibition to a greater extent than ChAdOx1-S. After 30 μg of SCB-2019 + CpG + aluminium hydroxide, titers against wild-type S-protein were significantly higher than after ChAdOx1-S on days 15 and 29, as were titers of neutralizing antibodies against the wild-type strain and Beta, Gamma, Delta, and Omicron variants. Boosting with SCB-2019 or ChAdOx1-S was well tolerated, with no vaccine-related serious or severe adverse events. Conclusions: Boosting ChAdOx1-S-primed adults with SCB-2019 induced higher levels of antibodies against a wild-type strain and SARS-CoV-2 variants than a homologous ChAdOx1-S booster, with the highest responses being with the 30-μg SCB-2019 + CpG + aluminium hydroxide formulation. Clinical Trials Registration: NCT05087368